2008
DOI: 10.2337/db07-1615
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism In Vivo in Four Commonly Used Inbred Mouse Strains

Abstract: OBJECTIVE-To characterize differences in whole-body glucose metabolism between commonly used inbred mouse strains.RESEARCH DESIGN AND METHODS-Hyperinsulinemic-euglycemic (ϳ8.5 mmol/l) and -hypoglycemic (ϳ3.0 mmol/l) clamps were done in catheterized, 5-h-fasted mice to assess insulin action and hypoglycemic counter-regulatory responsiveness. Hyperglycemic clamps (ϳ15 mmol/l) were done to assess insulin secretion and compared with results in perifused islets.RESULTS-Insulin action and hypoglycemic counter-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
204
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(234 citation statements)
references
References 33 publications
18
204
1
Order By: Relevance
“…Our findings stand in contrast to a recent study that examined the effects of full-length IGF1 modified with the addition of polyethylene glycol (PEG-IGF1) treatment in Mecp2 KO mice (Mecp2 tm1.1Bird ) on a mixed background (B6129S6F1) and showed variable effects, in particular on body weight, metabolism, and lifespan (37). However, it is well established that the same genetic manipulation can exhibit profoundly different phenotypes when present on different genetic backgrounds (38), and the 129 strains exhibit anomalous glucose and insulin metabolism (39,40). Indeed, Mecp2 KO mice (Mecp2 tm1.1Bird ) when mixed with 129 strains show an increase in body weight, whereas the same KO animals maintained on a C57BL/6 background have lower body weight (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings stand in contrast to a recent study that examined the effects of full-length IGF1 modified with the addition of polyethylene glycol (PEG-IGF1) treatment in Mecp2 KO mice (Mecp2 tm1.1Bird ) on a mixed background (B6129S6F1) and showed variable effects, in particular on body weight, metabolism, and lifespan (37). However, it is well established that the same genetic manipulation can exhibit profoundly different phenotypes when present on different genetic backgrounds (38), and the 129 strains exhibit anomalous glucose and insulin metabolism (39,40). Indeed, Mecp2 KO mice (Mecp2 tm1.1Bird ) when mixed with 129 strains show an increase in body weight, whereas the same KO animals maintained on a C57BL/6 background have lower body weight (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…C57/Bl6 is a widely used strain in metabolic studies. These mice are prone to insulin resistance and obesity, and are known to differ from other mouse strains in their insulin and glucose responses [36]. Hence, it is possible that this strain offers a more sensitive background on which to assess the effects of genetic mutations affecting molecular components that regulate insulin and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, when creating genetically manipulated mice, consideration must be given to the genetic background on which the mouse is created and differences in metabolic phenotype that might be associated with gene manipulation on mixed genetic backgrounds. Several previous studies have shown that mouse strains can differ substantially in their metabolic phenotype under normal low-fat diet (LFD) conditions and in response to a high-fat diet (HFD) [1][2][3][4][5]. Some problems with these and other previous strain comparisons are the use of diverse HFDs varying in lipid and carbohydrate content and the investigation of limited variables that may underpin the development of metabolic disease and importantly some contradictory findings.…”
Section: Introductionmentioning
confidence: 99%